A dual active site loaded silica aerogel and a method of preparation
Patent Information
- Application Number
- CN202410829541.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-25
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-06-25
AI Technical Summary
本发明的负载双活性位点的二氧化硅气凝胶具有高吸附容量和高吸附速率,可以高效吸附氨气,有效解决孔径阻塞和活性位点少而导致吸附性能不高的问题,为工业氨气吸附材料提供了新的思路
[0028](1)本发明制备的负载双活性位点的二氧化硅气凝胶具有高孔隙率、充足的活性位点,因此吸附容量大、吸附速率快,通过负载双活性位点有效解决了孔隙阻塞和活性位点少而导致吸附性能不高的问题(引入粒径远远小于磺酸基团的锌离子活性位点,解决了孔隙阻塞问题;负载双活性位点解决了位点不足问题,同时高效提升了吸附速率和吸附容量),为工业氨气吸附材料提供了新的思路。
Smart Images

Figure CN118558291B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ammonia adsorption technology, and in particular to a silica aerogel loaded with dual active sites and its preparation method. Background Technology
[0002] Ammonia (NH3), a widely used alkaline chemical in industry, is highly corrosive, volatile, and flammable and explosive. In industrial production, ammonia is commonly used in the manufacture of fertilizers, refrigeration technology, and the synthesis of other chemicals. However, its widespread use is accompanied by potential hazards and safety challenges. The harm caused by ammonia to the human respiratory system and eyes is significant; its strong corrosive properties damage the respiratory tract and mucous membranes, potentially leading to serious health problems and long-term impacts on the surrounding environment and communities. Therefore, there is an urgent need to develop an efficient method for treating ammonia to maintain it within a relatively safe concentration range.
[0003] Currently, the main technologies for separating and removing ammonia from mixed gases include biological methods, catalytic oxidation methods, plasma methods, and adsorption methods. Among these, adsorption methods have attracted attention due to their advantages such as low cost, ease of processing, recyclability, zero hazard, and simple operation. Adsorption methods generally include physical adsorption and chemical adsorption. Physical adsorption relies solely on the high specific surface area of the material to adsorb ammonia into the porous structure. Physical adsorption is caused by van der Waals forces between adsorbate and adsorbent molecules, resulting in weaker binding forces, lower heat of adsorption, easy desorption, and reversibility. Chemical adsorption, on the other hand, is caused by chemical bonds between the adsorbate and adsorbent. It involves the transfer, exchange, or sharing of electrons between adsorbate molecules and solid surface atoms (or molecules), forming adsorption chemical bonds. This is often irreversible, with typically higher heat of adsorption and greater difficulty in desorption, exhibiting stronger selectivity. Generally, the degree of physical adsorption is lower than that of chemical adsorption. The adsorption of ammonia by porous materials is a monolayer physical adsorption, relying solely on the high specific surface area of the material to adsorb ammonia into the porous structure. Therefore, the preparation of chemical adsorbents is key to improving adsorption performance.
[0004] Gas adsorption materials mainly include activated carbon, molecular sieves, metal-organic frameworks, and aerogels. Silica aerogels, due to their advantages such as high surface area, high porosity, low cost, good stability, easy surface modification, lightweight, excellent thermal insulation properties, and pore size smaller than gas molecules (less than 70 nm), are considered excellent porous carriers among high-performance adsorbents and have been widely used in the field of gas adsorption in recent years. However, for ammonia adsorption, there are still problems with relatively low adsorption rate and adsorption capacity. Summary of the Invention
[0005] The purpose of this invention is to provide a silica aerogel loaded with two active sites and its preparation method, thereby solving the problems existing in the prior art. The silica aerogel loaded with two active sites of this invention has high adsorption capacity and high adsorption rate, and can efficiently adsorb ammonia gas, effectively solving the problems of pore blockage and insufficient adsorption performance caused by a small number of active sites, thus providing a new approach for industrial ammonia adsorption materials.
[0006] To achieve the above objectives, the present invention provides the following solution:
[0007] One of the technical solutions of the present invention: a method for preparing silica aerogel loaded with dual active sites, comprising the following steps:
[0008] After the silicon source, organic solvent, water and mercaptosilane coupling agent are mixed evenly, an acid solution is added dropwise to catalyze the hydrolysis reaction, and then an alkaline solution is added dropwise to catalyze the condensation reaction to form a wet gel.
[0009] The wet gel was aged and then oxidized, followed by impregnation in a metal salt solution to obtain the silica aerogel loaded with dual active sites.
[0010] Furthermore, the silicon source includes tetraethyl orthosilicate, n-methylsilane, or methyl orthosilicate;
[0011] The mercaptosilane coupling agent includes 3-mercaptopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane or 3-mercaptopropylmethyldimethoxysilane;
[0012] The organic solvent includes ethanol.
[0013] Furthermore, the molar ratio of the silicon source, organic solvent, water and mercaptosilane coupling agent is 1:5:4:(0.1~0.5).
[0014] Furthermore, the acid solution includes hydrochloric acid solution, nitric acid solution, sulfuric acid solution, or acetic acid solution;
[0015] The alkaline solution includes sodium hydroxide solution, potassium hydroxide solution, or ammonia water.
[0016] Furthermore, the catalytic hydrolysis reaction takes 8–16 hours;
[0017] The catalytic polycondensation reaction takes 1 to 6 hours.
[0018] Furthermore, the aging temperature is 60°C, and the time is 12–24 hours;
[0019] The oxidation specifically includes: oxidizing the aged wet gel in a hydrogen peroxide solution for 24 hours.
[0020] Furthermore, the hydrogen peroxide solution is composed of hydrogen peroxide and anhydrous ethanol in a volume ratio of 1:1.
[0021] Furthermore, the metal salt solution is a zinc chloride solution;
[0022] The concentration of the zinc chloride solution is 10–60 wt%.
[0023] Using the parameters and conditions of this invention (temperature, time, dosage, etc.), the silica aerogel loaded with dual active sites prepared has the best structure, the best morphology, and the highest adsorption performance.
[0024] The second technical solution of the present invention: a silica aerogel loaded with dual active sites prepared by the above preparation method.
[0025] The third technical solution of the present invention: the application of the above-mentioned silica aerogel loaded with dual active sites in waste gas absorption.
[0026] Furthermore, the exhaust gas includes ammonia.
[0027] The present invention discloses the following technical effects:
[0028] (1) The silica aerogel loaded with dual active sites prepared by the present invention has high porosity and sufficient active sites, thus it has a large adsorption capacity and fast adsorption rate. By loading dual active sites, the problems of pore blockage and low adsorption performance caused by insufficient active sites are effectively solved (the introduction of zinc ion active sites with a particle size much smaller than sulfonic acid groups solves the pore blockage problem; loading dual active sites solves the problem of insufficient sites, and at the same time, it efficiently improves the adsorption rate and adsorption capacity), providing a new idea for industrial ammonia adsorption materials.
[0029] (2) The silica aerogel loaded with dual active sites of the present invention uses silica aerogel as the main component, which has a low cost. Furthermore, the silica aerogel loaded with dual active sites prepared by the present invention has high porosity, sufficient active sites, and large adsorption capacity. Attached Figure Description
[0030] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0031] Figure 1 This is a schematic diagram of the preparation process of the silica aerogel loaded with dual active sites according to the present invention;
[0032] Figure 2This is a SEM image of the silica aerogel loaded with dual active sites prepared in Example 2 of the present invention. Detailed Implementation
[0033] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0034] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0035] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0036] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be obvious to those skilled in the art. This specification and embodiments are merely exemplary.
[0037] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0038] A schematic diagram of the preparation process of the silica aerogel loaded with dual active sites of the present invention is shown below. Figure 1 .
[0039] Example 1
[0040] A method for preparing silica aerogel loaded with dual active sites:
[0041] (1) Measure 44 mL of tetraethyl orthosilicate (0.2 mol), 58 mL of anhydrous ethanol (1 mol), 14.4 mL of deionized water (0.8 mol), and 14.8 mL of 3-mercaptopropyltriethoxysilane (0.06 mol), and stir at a constant temperature for 6 h with a magnetic stirrer until completely dissolved to obtain mixed solution 1.
[0042] (2) Measure 50 mL of 85 wt% hydrochloric acid and 50 mL of anhydrous ethanol, mix them evenly to obtain an acid solution.
[0043] (3) The acid solution and mixed solution 1 were titrated in a co-current manner, and the silicon source was catalytically hydrolyzed at room temperature for 12 hours to obtain mixture A.
[0044] (4) Measure 59 mL of 99.8 wt% ammonia water and mix it with 50 mL of anhydrous ethanol to obtain an alkaline solution.
[0045] (5) Titrate the alkaline solution and mixture A in a parallel flow manner to adjust the pH of the mixed liquid to neutral to obtain mixture B. Then let mixture B stand for 2 hours to form a wet gel.
[0046] (6) The wet gel was aged in anhydrous ethanol solution at 60℃ for 24h, and then immersed in hydrogen peroxide solution (hydrogen peroxide solution is composed of 30wt% H2O2 and anhydrous ethanol in a volume ratio of 1:1) for 24h for oxidation. After oxidation, the sample was repeatedly washed with ethanol and finally dried at 120℃ for 24h to obtain sulfonic acid modified silica dry gel (acid modified silica aerogel).
[0047] (7) Take 10g of zinc chloride with a purity of 99.8% and dissolve it in 114.1mL of anhydrous ethanol. Mix well to obtain a zinc chloride solution with a concentration of 10wt%.
[0048] Sulfonic acid-modified silica aerogel was immersed in zinc chloride solution for 24 hours. After immersion, it was repeatedly washed with anhydrous ethanol to obtain zinc ion-modified silica aerogel. It was then air-dried at room temperature to obtain silica aerogel loaded with dual active sites.
[0049] Example 2
[0050] A method for preparing silica aerogel loaded with dual active sites:
[0051] (1) Measure 44 mL of tetraethyl orthosilicate (0.2 mol), 58 mL of anhydrous ethanol (1 mol), 14.4 mL of deionized water (0.8 mol), and 20.6 mL of 3-mercaptopropyltriethoxysilane (0.084 mol), and stir at a constant temperature for 6 h with a magnetic stirrer until completely dissolved to obtain mixed solution 1.
[0052] (2) Measure 50 mL of 85 wt% hydrochloric acid and 50 mL of anhydrous ethanol, mix them evenly to obtain an acid solution.
[0053] (3) The acid solution and mixed solution 1 were titrated in a co-current manner, and the silicon source was catalytically hydrolyzed at room temperature for 12 hours to obtain mixture A.
[0054] (4) Measure 59 mL of 99.8 wt% ammonia water and mix it with 50 mL of anhydrous ethanol to obtain an alkaline solution.
[0055] (5) Titrate the alkaline solution and mixture A in a parallel flow manner to adjust the pH of the mixed liquid to neutral to obtain mixture B. Then let mixture B stand for 2 hours to form a wet gel.
[0056] (6) The wet gel was aged in anhydrous ethanol at 60°C for 24 hours, and then immersed in hydrogen peroxide solution (hydrogen peroxide solution is composed of 30wt% H2O2 and anhydrous ethanol in a volume ratio of 1:1) for 24 hours for oxidation. After oxidation, the sample was repeatedly washed with ethanol and finally dried at 120°C for 24 hours to obtain sulfonic acid modified silica dry gel (acid modified silica aerogel).
[0057] (7) Take 10g of zinc chloride with a purity of 99.8% and dissolve it in 114.1mL of anhydrous ethanol. Mix well to obtain a zinc chloride solution with a concentration of 10wt%.
[0058] Sulfonic acid-modified silica aerogel was immersed in zinc chloride solution for 24 hours. After immersion, it was repeatedly washed with anhydrous ethanol to obtain zinc ion-modified silica aerogel. It was then air-dried at room temperature to obtain silica aerogel loaded with dual active sites.
[0059] The SEM morphology of the silica aerogel loaded with dual active sites prepared in this embodiment is shown in the figure. Figure 2 .
[0060] Example 3
[0061] A method for preparing silica aerogel loaded with dual active sites:
[0062] (1) Measure 44 mL of tetraethyl orthosilicate (0.2 mol), 58 mL of anhydrous ethanol (1 mol), 14.4 mL of deionized water (0.8 mol), and 20.6 mL of 3-mercaptopropyltriethoxysilane (0.084 mol), and stir at a constant temperature for 6 h with a magnetic stirrer until completely dissolved to obtain mixed solution 1.
[0063] (2) Measure 50 mL of 85 wt% hydrochloric acid and 50 mL of anhydrous ethanol, mix them evenly to obtain an acid solution.
[0064] (3) The acid solution and mixed solution 1 were titrated in a co-current manner, and the silicon source was catalytically hydrolyzed at room temperature for 12 hours to obtain mixture A.
[0065] (4) Measure 59 mL of 99.8 wt% ammonia water and mix it with 50 mL of anhydrous ethanol to obtain an alkaline solution.
[0066] (5) Titrate the alkaline solution and mixture A in a parallel flow manner to adjust the pH of the mixed liquid to neutral to obtain mixture B. Then let mixture B stand for 2 hours to form a wet gel.
[0067] (6) The wet gel was aged in anhydrous ethanol at 60°C for 24 hours, and then immersed in hydrogen peroxide solution (hydrogen peroxide solution is composed of 30wt% H2O2 and anhydrous ethanol in a volume ratio of 1:1) for 24 hours for oxidation. After oxidation, the sample was repeatedly washed with ethanol and finally dried at 120°C for 24 hours to obtain sulfonic acid modified silica dry gel (acid modified silica aerogel).
[0068] (7) Take 20g of zinc chloride with a purity of 99.8% and dissolve it in 101.4mL of anhydrous ethanol. Mix well to obtain a zinc chloride solution with a concentration of 20wt%.
[0069] Sulfonic acid-modified silica aerogel was immersed in zinc chloride solution for 24 hours. After immersion, it was repeatedly washed with anhydrous ethanol to obtain zinc ion-modified silica aerogel. It was then air-dried at room temperature to obtain silica aerogel loaded with dual active sites.
[0070] Example 4
[0071] A method for preparing silica aerogel loaded with dual active sites:
[0072] (1) Measure 44 mL of tetraethyl orthosilicate (0.2 mol), 58 mL of anhydrous ethanol (1 mol), 14.4 mL of deionized water (0.8 mol), and 20.6 mL of 3-mercaptopropyltriethoxysilane (0.084 mol), and stir at a constant temperature for 6 h with a magnetic stirrer until completely dissolved to obtain mixed solution 1.
[0073] (2) Measure 50 mL of 85 wt% hydrochloric acid and 50 mL of anhydrous ethanol, mix them evenly to obtain an acid solution.
[0074] (3) The acid solution and mixed solution 1 were titrated in a co-current manner, and the silicon source was catalytically hydrolyzed at room temperature for 12 hours to obtain mixture A.
[0075] (4) Measure 59 mL of 99.8 wt% ammonia water and mix it with 50 mL of anhydrous ethanol to obtain an alkaline solution.
[0076] (5) Titrate the alkaline solution and mixture A in a parallel flow manner to adjust the pH of the mixed liquid to neutral to obtain mixture B. Then let mixture B stand for 2 hours to form a wet gel.
[0077] (6) The wet gel was aged in anhydrous ethanol at 60°C for 24 hours, and then immersed in hydrogen peroxide solution (hydrogen peroxide solution is composed of 30wt% H2O2 and anhydrous ethanol in a volume ratio of 1:1) for 24 hours for oxidation. After oxidation, the sample was repeatedly washed with ethanol and finally dried at 120°C for 24 hours to obtain sulfonic acid modified silica dry gel (acid modified silica aerogel).
[0078] (7) Take 30g of zinc chloride with a purity of 99.8% and dissolve it in 88.7mL of anhydrous ethanol. Mix well to obtain a zinc chloride solution with a concentration of 30wt%.
[0079] Sulfonic acid-modified silica aerogel was immersed in zinc chloride solution for 24 hours. After immersion, it was repeatedly washed with anhydrous ethanol to obtain zinc ion-modified silica aerogel. It was then air-dried at room temperature to obtain silica aerogel loaded with dual active sites.
[0080] Comparative Example 1
[0081] Same as Example 2, except that the amount of 3-mercaptopropyltrimethoxysilane added in step (1) is 26.5 mL (0.1 mol).
[0082] Comparative Example 2
[0083] Same as Example 2, except that step (7) is omitted, i.e., it is not immersed in zinc oxide solution.
[0084] Comparative Example 3
[0085] Same as Example 2, except that 3-mercaptopropyltriethoxysilane was not added in step (1), the oxidation treatment in step (6) was omitted, and step (7) was omitted, that is, it was not immersed in zinc oxide solution.
[0086] Comparative Example 4
[0087] Same as Example 2, except that 24.6 mL (0.1 mol) of 3-mercaptopropyltriethoxysilane was added in step (1).
[0088] Example of effect 1
[0089] The specific surface area and average pore size of the silica aerogels prepared in the examples and comparative examples were measured, and the results are shown in Table 1.
[0090] Table 1 Specific surface area and average pore size
[0091]
[0092]
[0093] As can be seen from Table 1, the silica aerogel loaded with excessive acidic groups in Comparative Example 1 has the worst pore structure; the silica aerogel loaded with a small amount of acidic groups (using a small amount of 3-mercaptopropyltriethoxysilane) in Example 1 has the largest specific surface area and pore size, but the adsorption capacity is poor due to insufficient active sites (Table 2); the pore structure and active site conditions in Example 2 are the best.
[0094] Example 2
[0095] The ammonia adsorption performance of the silica aerogels prepared in the examples and comparative examples was determined.
[0096] Measurement method: Under normal pressure and inert gas protection at 150℃, 1g of silica aerogel was activated for 2h. After activation with a constant inlet concentration, the mixture was cooled to room temperature and then NH3 and N2 were introduced. The concentration of NH3 was 1000ppm, and the volumetric flow rate of the NH3 and N2 mixture was 200mL·min⁻¹. 1 .
[0097] The adsorption breakthrough curve was determined using the built-in thermal conductivity detector of the adsorption breakthrough curve analyzer. The amount of NH3 adsorbed was calculated based on the breakthrough curve, using the following formula:
[0098]
[0099] F act =Fo out ×C act (2)
[0100] Fo * =Fo out ×Co * (3)
[0101]
[0102] Among them, Fo out For total outflow, sccm; q ref The flow rate of the reference gas (helium), expressed in sccm; C ref The percentage concentration (%) of the reference gas (helium) at a given moment;
[0103] F act The outlet flow rate of the activation gas (nitrogen), sccm; C act The percentage concentration (%) of the activating gas (nitrogen) at a given moment;
[0104] Fo* is the outlet flow rate of the adsorbate at a certain moment, sccm;
[0105] Q* represents the amount of adsorbate adsorbed by the adsorbent, mL / g; t represents the total time from the start to the end of adsorption, s; Fi* represents the inlet flow rate of the adsorbate at a certain moment, sccm; m represents the mass of the adsorbent, g.
[0106] Co* represents the outlet concentration of the adsorbate at a given time, in percentages (%); F nob The outlet flow rate of the activation gas is sccm.
[0107] The ammonia adsorption performance of the silica aerogels prepared in the examples and comparative examples was determined.
[0108] The adsorbent is silica aerogel, and the adsorbate is NH3. The test results are shown in Table 2.
[0109] Table 2 Adsorption effect on ammonia
[0110]
[0111] In Table 2, 5% refers to the volume percentage of NH3 passing through the silica aerogel compared to the volume of NH3 before adsorption; 95% refers to the volume percentage of NH3 passing through the silica aerogel compared to the volume of NH3 before adsorption.
[0112] As shown in Table 2, compared with other examples and comparative examples, Example 2 showed the best adsorption effect (Example 2 achieved an ammonia adsorption capacity of 5.14 mmol·g at ambient pressure and temperature). -1 ).
[0113] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A method for preparing silica aerogel loaded with dual active sites, characterized in that, The steps are as follows: After the silicon source, organic solvent, water and mercaptosilane coupling agent are mixed evenly, an acid solution is added dropwise to catalyze the hydrolysis reaction, and then an alkaline solution is added dropwise to catalyze the condensation reaction to form a wet gel. After aging the wet gel, it was oxidized and then impregnated in a metal salt solution. After impregnation, it was repeatedly washed with anhydrous ethanol and air-dried at room temperature to obtain the silica aerogel loaded with dual active sites. The oxidation specifically includes: oxidizing the aged wet gel in a hydrogen peroxide solution for 24 hours; The metal salt solution is a zinc chloride solution; The mercaptosilane coupling agent is 3-mercaptopropyltriethoxysilane; The molar ratio of the silicon source, organic solvent, water and mercaptosilane coupling agent is 1:5:4:(0.1~0.5).
2. The preparation method according to claim 1, characterized in that, The silicon source includes tetraethyl orthosilicate or methyl orthosilicate; The organic solvent includes ethanol.
3. The preparation method according to claim 1, characterized in that, The acid solution includes hydrochloric acid solution, nitric acid solution, sulfuric acid solution or acetic acid solution; The alkaline solution includes sodium hydroxide solution, potassium hydroxide solution, or ammonia water.
4. The preparation method according to claim 1, characterized in that, The catalytic hydrolysis reaction takes 8–16 hours; The catalytic polycondensation reaction takes 1 to 6 hours.
5. The preparation method according to claim 1, characterized in that, The aging temperature is 60℃, and the time is 12 to 24 hours.
6. The preparation method according to claim 1, characterized in that, The concentration of the zinc chloride solution is 10–60 wt%.
7. A silica aerogel loaded with dual active sites prepared by the preparation method according to any one of claims 1 to 6.
8. The application of the silica aerogel with dual active sites as described in claim 7 in waste gas absorption.
9. The application according to claim 8, characterized in that, The waste gas includes ammonia.
Citation Information
Patent Citations
Sulfonyl modified silicon dioxide aerogel as well as preparation method and application thereof
CN113620302A